Utilization of lampirong (Placuna placenta) shells as adsorbent of methylene blue in aqueous solutions. - Tardaguela, Don Rey N.
Methylene Blue (MB) is a synthetic dye often discarded to bodies of water which has a negative effect towards the environment and ecosystem. Adsorption is one of the conventional water treatment techniques that is often used for dye removal. In this study, lampirong (Placuna placenta) shell-based adsorbent was synthesized through calcination for the removal of MB in aqueous solution. The successful synthesis of CLS was observed through the analysis of surface morphology, surface functional groups, and pHPZC. The pHPZC of the adsorbent was identified to be around 8.08 which shows a greater MB adsorption in alkaline conditions. In the parametric study, it was observed that the initial MB concentration, solution pH, and adsorbent dosage has a significant effect on MB removal. Based on the parametric study, the desired conditions for high MB removal efficiency were at initial MB concentration (5 ppm), solution pH (10), and adsorbent dosage (5 g L-1>). Nonlinear kinetic and isotherm modelling were performed on the experimental data obtained. The pseudo-second-order kinetic model (with a correlation coefficient of 0.9930) provides the best fit on the kinetic data. On the other hand, the Langmuir isotherm model (with a correlation coefficient of 0.9969) was the most suitable model for fitting the isotherm study. The maximum adsorption capacity of CLS in MB adsorption was 1.1028 mg g-1. Based on the kinetic and isotherm model, MB adsorption using CLS followed by a monolayer chemisorption process. These findings demonstrate that CLS can be an effective adsorbent for MB in aqueous solution.